ANALISIS OPERATING LEVERAGE (DOL), FINANCIAL LEVERAGE (DFL), DAN COMBINATION LEVERAGE (DCL) TERHADAP EARNING PER SHARE (EPS) PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Siti Mudawanah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2019)
The purpose of this study is to determine the effect of DOL on EPS, determine the effect of DFL on EPS, determine the effect of DCL on EPS and determine the effect of DOL, DFL and DCL on EPS. Adhi Karya (Persero) Tbk (ADHI), Elnusa Tbk (ELSA), Waskita Concrete Precast Tbk (WSBP), which came out of the LQ45 index calculation for this period. List of companies included in the 45 LQ45 Latest Stock Indexes (August 2019 - January 2020). Increased competition among companies in developing their companies so that the companies they manage have good value and good performance require companies to continue to make efforts to achieve with good strategies and proper financial management so that they are superior to other companies.The method used in this research is quantitative method. The research population to be carried out by researchers is all companies listed on the LQ45 index on the Indonesia Stock Exchange in 2017 - 2018, and the sample techniques used in this study are using purposive sampling techniques and selected by 29 companies. In this study the data were processed using SPSS V.20 software. To test the data using multiple linear regression analysis.The findings of this study are that DOL significantly influences EPS. However, DFL and DCL do not have a significant effect on EPS, and simultaneously DOL, DFL and DCL have a significant effect on EPS.